Principles of economics - Stevenson, Betsey; Wolfers, Justin (New York Worth Publishers, 2023)
Comprehensive coverage of the fundamental principles of economics, covering both microeconomics and macroeconomics, with emphasis on real-world examples from the business world and the everyday economics affecting us all. Includes a detailed presentation of the process of graphing, allowing students to work through economic problems graphically"--